Systemic Delivery of Magnetogene Nanoparticle Vector for Gene Expression in Hypoxic Tumors - Luis Daniel Terrazas-Armendáriz; Cynthia Aracely Alvizo-Báez; Itza Eloisa Luna-Cruz; Becky Annette Hernández-González; Ashanti Concepción Uscanga-Palomeque; Mitchel Abraham Ruiz-Robles; Eduardo Gerardo Pérez Tijerina; Cristina Rodríguez-Padilla; Reyes Tamez-Guerra; Juan Manuel Alcocer-González (MDPI AG, 2023)
Cancer is a disease that causes millions of deaths per year worldwide because conventional treatments have disadvantages such as unspecific tumor selectivity and unwanted toxicity. Most human solid tumors present hypoxic microenvironments and this promotes multidrug resistance. In this study, we present "Magnetogene nanoparticle vector" which takes advantage of the hypoxic microenvironment of solid tumors to increase selective gene expression in tumor cells and reduce unwanted toxicity in healthy cells; this vector was guided by a magnet to the tumor tissue. Magnetic nanoparticles (MNPs), chitosan (CS), and the pHRE-Luc plasmid with a hypoxia-inducible promoter were used to synthesize the vector called "Magnetogene nanoparticles" by ionic gelation. The hypoxic functionality of Magnetogene vector nanoparticles was confirmed in the B16F10 cell line by measuring the expression of the luciferase reporter gene under hypoxic and normoxic conditions. Also, the efficiency of the Magnetogene vector was confirmed in vivo. Magnetogene was administered by intravenous injection (IV) in the tail vein and directed through an external magnetic field at the site of tumor growth in C57Bl/6 mice. A Magnetogene vector with a size of 50 to 70 nm was directed and retained at the tumor area and gene expression was higher at the tumor site than in the others tissues, confirming the selectivity of this vector towards hypoxic tumor areas. This nanosystem, that we called the "Magnetogene vector" for systemic delivery and specific gene expression in hypoxic tumors controlled by an external magnetic designed to target hypoxic regions of tumors, can be used for cancer-specific gene therapies.